Impactos ambientais sobre a fauna silvestre causados por estradas na região do oeste paulista e a efetividade das medidas mitigadoras - AZEVEDO, Flávio José de (2022)
This dissertation aims to present the environmental impacts on wild fauna resulting from roads in the western region of São Paulo, as well as mitigating measures to minimize this problem. The road works, despite their indispensability, compromise the environment, often bringing irreversible environmental impacts. Of course, roads are fundamental to economic development. Its construction, however, like any anthropic action, causes countless impacts to the environment, since it modifies the natural habitat of the fauna. Each new construction entails human flow in previously uninhabited places, making this same habitat vulnerable and, consequently, possibly resulting in the loss of species. Environmental impacts are, therefore, one of the most relevant factors in the loss of biodiversity around the world. Thus, for sustainable development, it is necessary to think of urgent measures for environmental preservation. Common solutions must be found, considering all the risks and adapting the ways of life to the least impacting patterns, using appropriate public policies for each case. It is hoped, therefore, that the economy and the environment can coexist in a harmonious and proportional way, enabling sustainable development, with the aim of not depleting the resources that are available today. There must always be viable measures to protect the fauna, because we also depend on it. It is essential to adopt urgent measures to preserve the environment. Sustainable development is the path to our survival and that of future generations.The ecologically balanced environment is everyone's right, as provided for in art. 225 of the Federal Constitution. In this way, it is also everyone's duty to promote environmental preservation.